Investigation the effect of Scrophularia striata hydroalcoholic Extract On Cell Death and Migration in Cervical Cancer Cell Line - Zafari, Jaber; Rajabbeigi, Elham; Mohaghegh Shalmani, Leila; Azarshin, Seyedeh Zohreh; Javani Jouni, Fatemeh; Mansouri, Vahid; Mohaghegh Shalmani, Hamid; Moravej Farshi, Hamideh (International Journal of Medical Toxicology and Forensic Medicine, 2023)
Background: With the growing interest in plant-derived chemotherapeutic agents, there has been a significant rise in research exploring a broad range of plants in recent years. Scrophularia striata has gained attention due to its extensive medical applications. This study aimed to investigate the effect of S. striata extract on HeLa cervical cancer cells, specifically their migration, apoptosis, and necrosis. Methods: We first cultured HeLa cells in Dulbecco’s Modified Eagle’s Medium (DMEM) supplemented with 10% FBS and 1% penicillin/streptomycin. We then examined the cytotoxicity of S. striata extract at varying concentrations (0, 1, 10, 100, 500, and 1000 μg/mL) using the MTT assay after 24 hours. We evaluated the extent of wound healing using a scratch assay and analyzed the apoptosis activity of the extract using flow cytometry. Results: Our results showed that S. striata extract (IC50: 433.8 μg/mL) significantly enhances wound healing (P≤0.01) in cervical cancer and promotes apoptosis and necrosis of HeLa cells. Conclusion: Our findings suggest that S. striata may serve as an effective treatment for cervical cancer by inducing cell death and reducing migration.